Essentials in intraoperative indocyanine green videoangiography assessment for intracranial aneurysm surgery: conclusions from 295 consecutively clipped aneurysms and review of the literature - Roessler, Karl; Krawagna, Maximilian; Dörfler, Arnd; Buchfelder, Michael; Ganslandt, Oliver (Neurosurgical Focus, 2014)
Indocyanine green (ICG) videoangiography (VA) in cerebral aneurysm surgery allows confirmation of blood flow in parent, branching, and perforating vessels as well as assessment of remnant aneurysm parts after clip application. A retrospective analysis and review of the literature were conducted to determine the current essential advantages of ICG-VA in aneurysm surgery.The authors retrospectively evaluated all aneurysm cases treated with the aid of intraoperative ICG-VA at a single institution between 2007 and 2013. They also analyzed the literature published since the initial description of ICG-VA in 2003.Two hundred forty-six procedures were performed in 232 patients harboring 295 aneurysms. The patients, whose mean age was 54 years, consisted of 159 women and 73 men. One hundred twenty-four surgeries were performed after subarachnoid hemorrhage, and 122 were performed for incidental aneurysms. Single aneurysms were clipped in 185 patients, and multiple aneurysms were clipped in 47 (mean aneurysm diameter 6.9 mm, range 2-40 mm). No complications associated with ICG-VA occurred. Intraoperative microvascular Doppler ultrasonography was performed before ICG-VA in all patients, and postoperative digital subtraction angiography (DSA) studies were available in 121 patients (52.2%) for retrospective comparative analysis. In 22 (9%) of 246 procedures, the clip position was modified intraoperatively as a consequence of ICG-VA. Stenosis of the parent vessels (16 procedures) or occlusion of the perforators (6 procedures), not detected by micro-Doppler ultrasonography, were the most common problems demonstrated on ICG-VA. In another 11 procedures (4.5%), residual perfusion of the aneurysm was observed and one or more additional clips were applied. Vessel stenosis or a compromised perforating artery occurred independent of aneurysm location and was about equally common in middle cerebral artery and anterior communicating artery aneurysms. In 2 procedures (0.8%), aneurysm puncture revealed residual blood flow within the lesion, which had not been detected by the ICG-VA. In the postoperative DSA studies, unexpected small (< 2 mm) aneurysm neck remnants, which had not been detected on intraoperative ICG-VA, were found in 11 (9.1%) of 121 patients. However, these remnants remained without consequence except in 1 patient with a 6-mm residual aneurysm dome, which was subsequently embolized with coils.In a large cohort of consecutive patients, ICG-VA proved to be a helpful intraoperative tool and led to a significant intraoperative clip modification rate of 15%. However, small, < 2-mm-wide neck remnants and a 6-mm residual aneurysm were missed by intraoperative ICG-VA in up to 10% of patients. Results in this study confirm that DSA is indispensable for postoperative quality assessment in complex aneurysm surgery.
EVALuna2:22828